2021
DOI: 10.1002/gps.5489
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric symptoms during the COVID‐19 outbreak in older adults with bipolar disorder

Abstract: Objectives Older adults with bipolar disorder (OABD) are vulnerable for a COVID‐19 infection via multiple pathways. It is essential for OABD to adhere to the COVID‐19 measures, with potential consequences for the psychiatric symptoms. This situation offers the unique opportunity to investigate factors of vulnerability and resilience that are associated with psychiatric symptoms in OABD. Methods This study included 81 OABD patients aged over 50 years. Factors measured at baseline in patients that participated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 37 publications
6
44
2
1
Order By: Relevance
“…In all these cases, the stress and daily rhythm disruptions of lockdowns and/or quarantine were presumed to be a trigger for the (first) onset of manic episodes. The fact that a previous study (Orhan et al, 2020) among older patient with BD found a decrease in manic symptoms, while in our younger-aged cohort we found an increase might be explained by the fact that younger people with BD are more vulnerable to life stressors than older adults. According to this inoculation-hypothesis, older adults are better able to deal with life-stressors because they simply have more experience with this (Knight et al, 2000).…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…In all these cases, the stress and daily rhythm disruptions of lockdowns and/or quarantine were presumed to be a trigger for the (first) onset of manic episodes. The fact that a previous study (Orhan et al, 2020) among older patient with BD found a decrease in manic symptoms, while in our younger-aged cohort we found an increase might be explained by the fact that younger people with BD are more vulnerable to life stressors than older adults. According to this inoculation-hypothesis, older adults are better able to deal with life-stressors because they simply have more experience with this (Knight et al, 2000).…”
Section: Discussioncontrasting
confidence: 78%
“…In the study by Orhan et al. ( 2020 ), among older (over age 50) patients with BD comparable results with the study we previously mentioned were found: No worsening of symptom levels were observed among these patients. Actually, symptom levels significantly decreased among these patients.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Studies thus far have reported that individuals with SMI have poorer sleep, 25 more difficulty coping, 26 , 27 and higher levels of (and slower recovery from 25 ) COVID-19-related stress, 25 , 26 , 28–30 anxiety, 25–30 depression, 25–30 loneliness, 26 and psychotic experiences 27 , 28 compared to individuals without psychiatric illness. However, there have been mixed findings, as some studies found no exacerbation of mood or psychotic symptoms in patients, 31 , 32 but rather an increase in self-reported well-being. 31 …”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, the psychological vulnerability had led to more NA for the elderlies during the pandemic ( 15 ). In particular, clinicians have conducted extensive studies on elderly patients with mood disorder ( 16 , 17 ) and dementia ( 18 ) during the pandemic, as these illnesses are often identified as severe mental disorders ( 19 ). Undoubtedly, these studies provided guidance for clinicians to treat such patients in a more targeted manner, thus helped them positively cope with their NA.…”
Section: Introductionmentioning
confidence: 99%